Accuracy of the Conventional Facial Impression Method and Three-Dimensional Auricular Shape Data Obtained Using Extra- and Intraoral Optical Scanners - Takumi Kasahara; Meiko Oki; Shingo Kamijo; Hidekazu Takahashi (Dentistry Journal)
Background: Facial impression methods have been used to fabricate auricular prostheses; however, deformation due to the weight of the impression material remains. This study aimed to investigate the accuracy of auricular three-dimensional (3D) data obtained using a 3D optical extraoral scanner and an intraoral scanner compared with that of a conventional facial impression method. Methods: Six auricles were digitized using an extraoral scanner with and without a reference board around the auricle and an intraoral scanner. Auricle casts fabricated using auricle impressions were scanned using a laboratory scanner. All obtained data were superimposed, and the 3D deformations of the different methods were evaluated using measurement mapping and root mean square (RMS) values. The length, width, and height of the auricular casts and scanned data were measured and compared with the sizes of the original auricles measured using a caliper. Results: Large displacements of the back and margins of the ears were observed, and the RMS values ranged from 0.5–2.4 mm. Larger widths and smaller heights of the scanned and impression data were observed compared to the anthropometric ear data. Conclusions: The study concluded that the fabrication of auricular prostheses using optical scanning is clinically acceptable. All examined scanning techniques demonstrated discrepancies within acceptable limits when compared to the conventional facial impression method.